Menang Jadi Arang, Kalah Jadi Abu: Motif Batik Tantri Harimau dan Banteng - Romy Setiawan; Dyanningrum Pradhikta (Journal of Innovation and Applied Technology, 2022)
The reliefs of animal stories carved in a number of temples in Java are derived from the collection of Tantri Stories, the origin of which is the Kamandaka Tantri story. One of them is the story of the tiger and the bull. It's not just sheep that can be pitted against each other, in the tantri story, the tiger and the bull are victims of a fight against each other. Besides the story is quite familiar, the moral message is universally applicable. The importance of the realization of the development of motifs on the product because it is an innovation and the application of design which is a design that has aesthetic and artistic value. Through the Tiger and Banteng batik motifs, this is one form of the artist's contribution to give hope as a person to maintain principles, be confident and wise in taking a stance.